Dry cleaning of InSb surfaces by hydrogen molecule exposure in ultrahigh vacuum - Jahanshah Rad, Zahra; Miettinen, Mikko; Punkkinen, Marko; Laukkanen, Pekka; Kokko, Kalevi (Elsevier B.V., 2025)
Cleaning semiconductor surfaces by atomic hydrogen or hydrogen plasma has gained significant interest because such a dry-cleaning method enables to reduce consumption of chemicals and pure water, and to treat challenging surfaces of three-dimensional semiconductor nanostructures. We have studied effects of mere H2 molecule exposures on (111)B and (110) surfaces of InSb with native oxides in an ultrahigh-vacuum (UHV) chamber. Without any hydrogen cracking, exposure of native-oxide covered InSb(111)B, heated simultaneously at 350 °C, to H2 with a partial pressure of 5∙10−5 mbar decreases amount of surface oxides and carbon, according to x-ray photoelectron spectroscopy, and provides (2×2) low-energy electron diffraction (LEED) pattern. Scanning tunneling microscopy indicates that this InSb(111)B(2×2) surface contains still extra Sb. When the InSb temperature increases to 400 °C during the H2 exposure, LEED changes to (3×3) pattern, which is known to arise from a less Sb-rich surface compared to InSb(111)B(2×2). When InSb(111)B(3×3) is exposed to H2 at the lowered temperature of 300 °C, LEED changes back to (2×2), which is discussed to arise from that InSb(111)B(3×3) contains still oxygen. Experiments for InSb(110) support that the found H2 exposure effects apply to different crystal faces of InSb.